Effects of gender-affirming hormones on diurnal cortisol concentrations: A prospective study - Margot W.L. Morssinkhof; David Matthew Doyle; Ysbrand D. van der Werf; Martin den Heijer; Annemieke Heijboer; Birit F.P. Broekman; Dirk Jan Stenvers (Neurobiology of Stress, 2025)
The diurnal rhythm of the hypothalamic-pituitary-adrenal (HPA) axis is essential for physical and mental health. There are sex differences in this diurnal rhythm, including steeper diurnal cortisol slopes in females compared to males, and sex hormones likely contribute to this difference. While previous studies found changes in HPA axis responsivity and serum cortisol in transgender people starting gender-affirming hormone therapy (GAHT), no study examined the effect of GAHT on diurnal salivary cortisol. This study examined sex differences in diurnal cortisol and changes in diurnal cortisol after three months of GAHT.We analyzed salivary cortisol levels in eleven transmasculine (TM) and seven transfeminine (TF) participants before GAHT and after three months of GAHT. Participants collected saliva samples at 30 min, 5.5 h and 10.5 h after awakening, and at bedtime. Absolute cortisol levels and diurnal cortisol slopes were compared between the groups at baseline, and in each group between baseline and three months of GAHT.Before starting GAHT, the TM group showed a steeper diurnal cortisol slope compared to the TF group. Neither the TM group nor the TF group showed any significant changes in cortisol levels or slopes after GAHT.We replicate previously reported sex differences in diurnal cortisol levels at baseline, but we find no significant changes in diurnal salivary cortisol after participants start GAHT. This could be associated with homeostatic adaptation of the HPA axis and cortisol-binding globulin concentrations. Future studies should focus on the role of bound and unbound cortisol and stress-related cortisol changes.